Maize-Nutrient-Manager: Training workshops, Songwe Regions, Tanzania - Kilakila, Mukoma Kitundu; Andersson, Jens A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Between 11 and 25 November 2020, several workshops were organized in Vwawa (Mbozi district) and Momba (Momba district), in the Songwe region of Tanzania. The workshops trained government extension workers in the use of the Maize-Nutrient-Manager (MNM) (version 2) mobile phone application for field-specific nutrient management advice. Forty-nine extension workers were trained, 38 and 11 from Mbozi and Momba district, respectively. Among the trained extension workers, 26 had participated in similar workshops in 2019. The training enables extension workers to provide fertiliser management advice for the upcoming 2020-21 season.